Tumbling : a novel - Carter, Caela (Viking, 2016)
They sacrificed their childhoods to compete in the two days of the U.S. Olympic Gymnastics Trials. Grace lives and breathes gymnastics-- but can never be perfect enough. Leigh has a gymnastics career, a normal high-school life... and a secret that could ruin everything. Camille wants to please her mom and her boyfriend... but most of all she wants to walk away. Wilhelmina was denied her Olympic dream four years ago, and she won't let anything stop her this time... anything. Monica is terrified: nobody believes in her-- and why should they? Some will be stars. Some will be going home with nothing. And all will have their lives changed forever....